PENERAPAN GOOD GOVERNANCE DALAM PELAYANAN PUBLIK (Studi Tentang Kualitas Pelayanan Elektronik Kartu Tanda Penduduk Berbasis Good) Governance Di Kecamatan Sukolilo Surabaya) - Cahyadi, Arif (Universitas 17 Agustus 1945 Surabaya, 2016)
In era globalization the state is expected to change for the better, one of them in the service of maintenance of manufacture Electronic Identity Card. In realizing the changes the government is expected to apply the principles of good governance in giving services must oriented to meeting the needs and satisfaction of the people. This research aims to determine the quality of service maintenance of manufacture Electronic Identity Card based on good governance. Data collection was conducted using questionnaires, interviews, and observations in the District Sukolilo Surabaya, questionnaires were distributed to the public as much as 25 informants. Methods for the data analysis is a data reduction, data presentation, and draw conclusions. The results of the study to get a whole that the implementation aspects of good governance to the dimensions of quality of public services have not felt very good satisfaction just people feel good.Keywords: good governance, the quality of service.